2005
DOI: 10.1063/1.1924693
|View full text |Cite
|
Sign up to set email alerts
|

Packing density and structure effects on energy-transfer dynamics in argon collisions with organic monolayers

Abstract: A combined experimental and molecular-dynamics simulation study has been used to investigate energy-transfer dynamics of argon atoms when they collide with n-alkanethiols adsorbed to gold and silver substrates. These surfaces provide the opportunity to explore how surface structure and packing density of alkane chains affect energy transfer in gas-surface collisions while maintaining the chemical nature of the surface. The chains pack standing up with 12 degrees and 30 degrees tilt angles relative to the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 34 publications
9
82
0
Order By: Relevance
“…Furthermore, molecular beams with energies much higher than thermal energies have been used in most detailed studies of gassurface scattering. [3][4][5] Nevertheless, such experiments have shown that a highly efficient solid-gas energy exchange occurs when the solid surface is modified with selfassembled monolayers (SAMs). 4,6,7 This suggests that even in the case of the scattering of the gas characterized by thermal energies, highly efficient thermal energy exchange can be achieved with SAM modified surfaces.…”
Section: Improvement Of Heat Transfer Efficiency At Solid-gas Interfamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, molecular beams with energies much higher than thermal energies have been used in most detailed studies of gassurface scattering. [3][4][5] Nevertheless, such experiments have shown that a highly efficient solid-gas energy exchange occurs when the solid surface is modified with selfassembled monolayers (SAMs). 4,6,7 This suggests that even in the case of the scattering of the gas characterized by thermal energies, highly efficient thermal energy exchange can be achieved with SAM modified surfaces.…”
Section: Improvement Of Heat Transfer Efficiency At Solid-gas Interfamentioning
confidence: 99%
“…The longer collision time and much higher TAC on the SAM surface indicate the Ar-SAM thermal energy exchange is mainly through the trappingdesorption channel in which the gas atoms lose memory of their incident parameters and thermalize with the surface upon desorption. 4 The longer collision time and better energy exchange might be caused by two factors associated with SAMs. One is the terminal pseudo-atoms in the SAM are much lighter than the Au atoms in the bare surface such that the gas atoms have better mass matching with CH 3 (m Ar /m CH3 % 2.6) compared to that with Au (m Ar /m Au % 0.2).…”
Section: Improvement Of Heat Transfer Efficiency At Solid-gas Interfamentioning
confidence: 99%
“…From this analysis we found 2610 complexes per Ag particle ( Table 2). The corresponding footprint of complexes on the 10 nm particle surface would be approximately 12 Å 2 /complex, which is relatively small and suggests that some complexes remain unbound forming a looped oligomeric structure above the metal surface [54,55].…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…62 For alkanethiol films with larger amounts of corrugation, more energy is deposited compared to less-corrugated samples. The low-frequency vibrational modes that are primarily responsible for energy accommodation are more accessible in the highly corrugated films, giving rise to a 7% increase in energy transferred.…”
Section: B Domain Boundary Annealingmentioning
confidence: 99%